Continuous Solvent/Detergent Virus Inactivation Using a Packed‐Bed Reactor. Issue 8 (23rd April 2019) - Martins, Duarte L.; Sencar, Jure; Hammerschmidt, Nikolaus; Tille, Björn; Kinderman, Johanna; Kreil, Thomas R.; Jungbauer, Alois
Abstract : Continuous virus inactivation (VI) remains one of the missing pieces while the biopharma industry moves toward continuous manufacturing. The challenges of adapting VI to the continuous operation are two‐fold: 1) achieving fluid homogeneity and 2) a narrow residence time distribution (RTD) for fluid incubation. To address these challenges, a dynamic active in‐line mixer and a packed‐bed continuous virus inactivation reactor (CVIR) are implemented, which act as a narrow RTD incubation chamber. The developed concept is applied using solvent/detergent (S/D) treatment for inactivation of two commonly used model viruses. The in‐line mixer is characterized and enables mixing of the viscous S/D chemicals to ±1.0% of the target concentration in a small dead volume. The reactor's RTD is characterized and additional control experiments confirm that the VI is due to the S/D action and not induced by system components. The CVIR setup achieves steady state rapidly before two reactor volumes and the logarithmic reduction values of the continuous inactivation process are identical to those obtained by the traditional batch operation. The packed‐bed reactor for continuous VI unites fully continuous processing with very low‐pressure drop and scalability. Abstract : Virus inactivation is essential for product safety; however, its implementation in continuous mode remains a challenge while the biopharma industry aims at continuous biomanufacturing. This work describes the f﻿ull viral inactivation of two model viruses by solvent/detergent using a packed‐bed reactor with narrow residence time distribution as an incubation reactor. This novel approach enables an undisrupted mass flow and truly continuous operation while being as effective as the current batch approach.